B133 Modified ipack block and blockade of the vastus lateralis and anterior femoral cutaneous nerve branches in total knee arthroplasty. (11th August 2022) - Singleton, J; Ramesh, V; Odeleye, A; Sebastian, M
Abstract : Background and Aims: Total knee arthroplasty (TKA) is associated with severe pain postoperatively (po). IPACK block can reduce pain and opioid consumption after TKA by covering all the articular branches of the knee with the exception of the Nerve to vastus lateralis (NVL), vastus intermedius (NVI) and branches of vastus medialis nerve (1–2). The blockade of the anterior femoral cutaneous nerve (ACFN) branches has also demonstrated an improvement in outcomes (3). Methods: We aim to evaluate the recovery and opioid consumption of five patients undergoing TKA following the same anaesthetic protocol. This included a 2 injections blockade of the knee. The first injection consisted of an IPACK block supplemented with a sub-sartorial deposition of LA to ensure the saphenous nerve blockade.The second injection included the blockade of NVL, NVI and the AFCN branches. Recovery was assessed by 'Quality of recovery' score (QoR15) (4) pre-operatively, on day 1, 2 and 7 po. Results: The time spent in moderate pain was reduced at all po time points compared with preop. The time spent in severe pain at 24 and 48 hours was not increased compared with preop. Three of the five patients required no rescue opioids. Among the others median oral morphine milligram equivalent was 50mg within 48h.All patients were mobile within the first 24h. Conclusions: The combination of modified IPACK, VLN, VIN and ACFN branches blockade as part of a multimodal analgesia reduced the time of moderate pain reported and did not increase the time spent in severe pain. It allowed for early ambulation with low opioid consumption.